(untitled) (Communications in Computational Chemistry, 2025)
Theoretical studies on some chlorinated pesticides compounds namely: Heptachlor, Heptachlorepoxide and Chlordane as a first group, Aldrin and Endrin as a second group, and DDT, Methoxychlor as a third group, were performed using semi-empirical quantum chemical calculation. Modified Neglect of Diatomic Overlap MNDO method was used to investigate the effect of positional variation of chlorine and oxygen atoms on the electronic and structure properties of the studied chlorinated pesticides. The structure optimization of some electronic parameters such as heats of formation, total energies, electronic energy, binding energy, nuclear energy, ionization energies, electron affinities and dipole moment were calculated and discussed. The energy of the Highest Occupied Molecular Orbital (HOMO) and the energy of the Lowest Unoccupied Molecular Orbital (LUMO) are also calculated. The LUMO-HOMO energy gap have been calculated and discussed. The stability and activity of the studied compounds based on the obtained values have been investigated.